Análise estrutural de tubos de concreto armado com resíduo de borracha de pneu - Trentin, Thiago Francisco Silva [UNESP] (2014)
The concrete material has a number of advantages like durability, low permeability, weather resistance and high compressive strength. These qualities have led its application to the rainwater collection, since the pipes are usually buried, and, thus, are subjected to compressive forces and exposed to the action of water. However, the concrete has some limitations, as, for example, low resistance to tensile stress, high self-weight, ease of cracking and a brittle behavior in rupture. Thus, many materials are being studied in order to be used as a new concrete component, seeking to minimize its disadvantages. One of them is the tire rubber residue. This residue is a fibrous material that takes a long time to decompose and increases the amount of trash in landfills, but it may give a greater deformation capacity and also a more effective distribution of stresses to the concrete. Furthermore, the tire rubber residue can provide an increase in energy absorption and a decrease in the propagation of cracks in the hardened state. However several studies show that the inclusion of tire rubber residue in the concrete causes a decrease in the mechanical strength to compression, a decrease in the workability of the mixtures and an increase of the content of entrained air. This work deals with the analysis of the structural behavior of five reinforced concrete pipes: one without the addition of tire rubber residue (designated as TC); two of them with an content of residue equal to 10 kg of residue per cubic meter of concrete (designated as TR 10); and the last two with a quantity of 20 kg per cubic meter of concrete (designated as TR 20). All the pipes had a nominal diameter of 60 cm and an effective length of 150 cm. In order to quantify the strength of the pipes, the diametral compression tests were performed according to the recommendations of the NBR 8890 (ABNT, 2007). The diametral displacements at the hub ...